The training of teachers-researchers in Special Education during the dictatorship in Brazil - Souza, Flávia Faissal de; Pletsch, Márcia Denise; Batista, Getsename de Freitas (Education Policy Analysis Archives, 2019)
Special Education institutionalization occurred under the dictatorship regime, with the creation of the National Center for Special Education (Cenesp), when there were agreements for teachers and researchers training in Special Education. The purpose of this article is to identify the influences of the UN international guidelines and their relationship to the MEC/Usaid agreements, in the Cenesp structuring educational proposals for the teachers-researchers training. For this, we conducted a documentary research and a semi-structured interview with the first director general of Cenesp. Our analysis, when discussing the international and national context from that time, problematizes the place of research and teacher training for Special Education.